Prioritizing Plants around the Cross-Border Area of Greece and the Republic of North Macedonia: Integrated Conservation Actions and Sustainable Exploitation Potential - Krigas, Nikos; Karapatzak, Eleftherios; Panagiotidou, Marina; Sarropoulou, Virginia; Samartza, Ioulietta; Karydas, Antonis; Damianidis, Christos K.; Najdovski, Boris; Teofilovski, Aco; Mandzukovski, Dejan; Brndevska Stipanović, Viktorija; Papanastasi, Katerina; et al. (MDPI AG, 2022)
Plants know no political borders and some of them are restricted to small geographical territories of different countries in which they are endemic. In this study, we prioritized plants (PPs) of the cross-border area of Greece and the Republic of North Macedonia that are already threatened or nearly so (PPA), those which occur exclusively on either side of borderline and/or nearby countries (PPB), or those which are uncommon and rare in this region (PPC) with the aim to document in-situ the species-specific risks-threats; offer ex-situ conservation for them as a back-up solution for future re-introductions and sustainable exploitation; and raise public awareness and alertness about the importance of local biodiversity. In the framework of the project Conse-pp, 20 botanical expeditions were performed in 75 selected areas to collect samples and suitable propagation material from 130 PPs (147 accession numbers), also recording all types of threats-identified in-situ for each of them. No ex-situ conservation was detected for 40 PPs worldwide while for another 12 PPs only limited attempts have been made to date. The fully documented PPs are currently maintained under ex- situ conservation and acclimatization in the Balkan Botanic Garden of Kroussia (BBGK). In total, 156 propagation trials (sexual or asexual) have been made for these PPs to develop species-specific propagation protocols. Consequently, the production of new plant stocks raised ex-situ was achieved (n = 3254 individuals; first-time ex-situ conservation for 40 taxa), and this has enabled the establishment of three awareness-raising sites with PPs: (i) 1000 plants of 70 PPs in the newly designed Kardia Botanical Park in Thermi (Greece); (ii) 850 plants of 104 PPs in the phytodiversity awareness spot in BBGK and 130 individual PPs in the Garden of Environmental Awareness; and (iii) 42 plants of 14 PP taxa delivered to the botanic garden of Ss. Cyril and Methodius University in Skopje. This project outlines the necessity of the development of common plant conservation strategies for threatened plants in cross-border areas of neighboring countries and presents an integrated approach allowing for sustainable development and future in-situ protection measures and actions in the studied cross-border area.
Original scientific article
Keywords: Conse-pp (INTERREG); in-situ conservation; ex-situ conservation; propagation protocols; Balkan vascular flora; threatened plant populations; local endemic plants; Mediterranean